(3UaI GdefGabs - (3GdaQjGHj , CHh HcQ LYaQ Hf eMeO Hf GdMSf Hf GdeSJaGV GdaQjGHj, GdaQjGHj,J (B301 (3g` s
(3ChdgG (B:s
(3bGdhG CfG CHh LYaQ eMeO s
(3BNQgG (B:s
(3BNQ GdLRA hGdMeO ddg hMOg s
(3HBNQg SeGYGJ cKjQI ai hQbJjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B127 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B146s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs